2014
DOI: 10.1371/journal.pone.0093299
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in the Prevalence of E. coli O157 in Cattle: A Meta-Analysis and Meta-Regression

Abstract: Background Escherichia coli O157 (EcO157) infection has been recognized as an important global public health concern. But information on the prevalence of EcO157 in cattle at the global and at the wider geographical levels is limited, if not absent. This is the first meta-analysis to investigate the point prevalence of EcO157 in cattle at the global level and to explore the factors contributing to variation in prevalence estimates.MethodsSeven electronic databases- CAB Abstracts, PubMed, Biosis Citation Index,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 149 publications
2
43
0
1
Order By: Relevance
“…Our results corroborated with the findings of Ogunleye et al (2013), but much lower than the findings of Masud et al (2012). Differences in geographical locations might be the reason for this as Islam et al (2014) reported a geographical variation in the prevalence of E. coli in cattle. The antimicrobial susceptibility patterns observed in the isolates from cattle of both management systems (intensive and Bathan) towards 10 antimicrobials summarized that the isolates were diverse in their antimicrobial resistance spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Our results corroborated with the findings of Ogunleye et al (2013), but much lower than the findings of Masud et al (2012). Differences in geographical locations might be the reason for this as Islam et al (2014) reported a geographical variation in the prevalence of E. coli in cattle. The antimicrobial susceptibility patterns observed in the isolates from cattle of both management systems (intensive and Bathan) towards 10 antimicrobials summarized that the isolates were diverse in their antimicrobial resistance spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search was conducted using similar techniques to Islam et al. () on 31 June 2014 using the Scopus database. The keyword search is provided in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To date, no studies have attempted to synthesize information from published and grey literature to quantify and compare the rate of H7N9 detection in birds compared to H5N1. Meta‐analysis and regression analysis have been used in previous studies to provide overall estimates of prevalence rates of an infectious pathogen in animal populations (Houe et al., ; Sanchez et al., ; Islam et al., ), and similar techniques were used for this study. We therefore aimed to conduct a meta‐analysis to estimate the overall prevalence of H5N1 and H7N9 in different bird populations, and to compare the prevalence of both viruses by other relevant variables.…”
Section: Introductionmentioning
confidence: 99%
“…In general, strategies for prevention and control of the spread of E. coli should include access to safe water, good handling practices to reduce the risk of food contamination, sanitation measures, public education and vaccination [38,39]. E. coli in the context of epidemiology as approached from a meta-analysis perspective involves prevalence issues [40,41] and reviews epidemic potential [42,43] of this pathogen as well as being a causative factor in diarrheal illness [44]. Given the variety of epidemiological areas of E. coli research warranting meta-analysis, it provides a fertile base of future undertakings in this area.…”
Section: Review Of E Coli Meta-analyses Based On Topicsmentioning
confidence: 99%
“…These included poultry [78], cattle [41,[69][70][71][72][79][80][81] and pigs [61,82]. Non-farm animals where E. coli studies have been meta-analyzed were mice [77].…”
Section: E Coli Meta-analyses Involving Non-human Animals and Plantsmentioning
confidence: 99%